Are Future Nurses Ready for Digital Health?: Informatics Competency Baseline Assessment - Kleib, Manal; Nagle, Lynn M; Furlong, Karen E; Paul, Pauline; Duarte Wisnesky, Uira; Ali, Shamsa (Nurse educator, 2022)
Research continues to show significant gaps in nursing graduates' preparedness in digital health. The aim of this study was to explore nursing students' self-perceived nursing informatics competency and preparedness in digital health, describe learning opportunities available, and identify perceived learning barriers and facilitators to developing informatics competency. A sequential mixed-methods design, using a cross-sectional survey and interviews, was used. Senior undergraduate students (n = 221) in BScN programs in a Western Canadian Province participated. Participants self-reported being somewhat competent in nursing informatics. Three themes were identified: struggling to make sense of informatics nursing practice; learning experiences; and preparedness for future practice. Addressing inconsistencies in informatics education is an urgent priority so that nursing graduates are competent upon joining the workforce. Implications for nursing education, practice, and policy are discussed.